Smart fuzzy incubator for free-range chicken on internet of things - Islamiyah, Mufidatul; Arifin, Samsul (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This paper presents the design of an artificial incubator for free-range chicken eggs. The incubator is designed to maintain optimal conditions and humidity for embryo development and this incubator is equipped with an egg turning mechanism. This incubator is designed using NodeMCU 8266 hardware which is used as a control that connects to the database server, and this incubator is built using multiplex, exhaust fan, mist maker, motor tuning, DS18B20, DHT-11 and real-time clock (RTC) DS3231. The temperature and humidity conditions in the incubator are maintained within the desired range and the egg changing mechanism works effectively. The results of this research show that this artificial incubator can be a reliable and effective tool for hatching free-range chicken eggs. This incubator is very easy to use and maintain and very affordable for local free-range chicken farming. This future research will focus on determining the conditions under which the incubator will provide the best results in terms of hatching efficiency for free-range chickens.